Articles by Florence O'Donoghue regarding the use of guerilla warfare in Ireland - O'Donoghue, Florence, 1895-1967; Bryan, Dan 1900–1985; An Cosantóir (Magazine) (1963)
Also includes two issues of An Cosantóir.
Keywords: Breen, Dan, -- 1894-1969; Lynch, Liam, -- 1893-1923; Irish Republican Army; Dublin Historical Association; Ireland -- History -- War of Independence, 1919-1921